Current research in advanced materials and processes : YUCOMAT VI proceedings of the 6th conference of the Yugoslav Materials Research Society held in Herceg Novi, Serbia and Montenegro, September 13-17 2004 - Uskokovic, Dragan P.; Milonjic, Slobodan K.; Rakovic, Dejan I. (Materials science forum, 2005)
The present book comprises ninety-two papers, by leading scientists from 21 countries, thematically arranged into ten sections: I Nanostructures and Thin Films; II Solid State Phenomena; III Nanomaterials; IV Advanced Materials; V Materials for Electrochemistry; VI Spectroscopic Characterization; VII Synthesis and Processing; VIII Powders, Ceramics and Sintering; IX Composites and X Biomaterials. The book is recommended to all researchers and students working in this fascinating scientific and technological field, as they cannot fail to find many fruitful and stimulating ideas in this rich vein of theoretical and experimental contributions.